Body Composition Impact on Sleep in Young Adults: The Mediating Role of Sedentariness, Physical Activity, and Diet - Carneiro-Barrera, Almudena (J Clin Med, 2020)
Obesity and sleep disturbances are both related to endocrine and metabolic alterations, cardiovascular disease, and impaired daytime functioning and mood. However, the bidirectional relationship between these conditions and the underlying mechanisms still remain unclear. This study aimed to investigate the potential association of anthropometric and body composition parameters with sleep in young adults, considering the mediating role of sedentariness, physical activity, and diet. A total of 187 adults aged 18–25 (35.29% men) participated in the study. Body mass index (BMI), waist–hip ratio, and waist–height ratio were calculated, and a dual-energy X-ray absorptiometry scanner was used to assess body composition. Sedentary time and physical activity, as well as sleep duration and quality, were objectively and subjectively measured using accelerometry and the Pittsburgh Sleep Quality Index. An inverse association was found between BMI and total sleep time (β = −0.165, p = 0.029). Waist–hip ratio and lean mass index were also negatively associated with total sleep time (β = −0.222, p = 0.007, and β = −0.219, p = 0.004) and sleep efficiency (β = −0.174, p = 0.037, and β = −0.188, p = 0.013). Sedentary time moderated by sex explained the association of BMI with total sleep time such that a high BMI was related to higher sedentariness in men which, in turn, was significantly associated with shorter sleep duration. Sedentary time is, therefore, a link/risk factor mediating the association of high BMI with short sleep duration in healthy young men.